Energy supply chain empowerment through tradable green and white certificates: A pathway to sustainable energy generation. (1st October 2022) - Safarzadeh, Soroush; Hafezalkotob, Ashkan; Jafari, Hamed
Graphical abstract: Highlights: A model is proposed to maximize market performance including tradable certificates. The long-term impacts of regulations on market are discussed by fine and subsidy. Three important objectives for government are investigated under four scenarios. The obtained results are validated by Turkey's energy data as a real case study. Fine policy is more effective than a subsidy to empower renewable electricity. Abstract: In the last decades, due to the increasing environmental concerns such as energy-resource depletion and global warming, energy efficiency instruments and renewable energy production has been promoted more than ever. This paper investigates a comprehensive comparison between two energy markets, i.e., the tradable white certificate (TWC) market and the tradable green certificate (TGC) market. How to coordinate the two energy markets and what the coordination impacts become the main issues under a reward-penalty mechanism. This multi-agent problem is discussed in an electricity supply chain consisting of two populations of traditional energy suppliers who want to decide about using one of them under government intervention. In this regard, the behavior of the suppliers is analyzed under three different Scenarios, including traditional power generation, energy efficiency program (EEP), and renewable portfolio standards (RPSs). An evolutionary game is applied to formulate the problem. The results show that a mandatory fine policy is more useful than an energy-saving subsidy to motivate the traditional suppliers to move toward sustainable energy generation. This policy also helps governments to meet their sustainable-oriented goals, as we discussed in this work. The findings can be applied to extend sustainable-based energy projects in developing countries.